Effects of Yoga on Quality of Life and Pain in Women With Chronic Pelvic Pain: Systematic Review and Meta-Analysis. Issue 3 (July 2019) - Russell, Natalie; Daniels, Bevin; Smoot, Betty; Allen, Diane D.
Abstract : Background: Chronic pelvic pain (CPP) is a multifactorial condition affecting 20% of women in the United States. Treatment includes pharmacological interventions, physical therapy, and lifestyle modifications. Previous studies show yoga effectively managing low back pain and pregnancy-related low back and pelvic pain, yet evidence related to CPP is limited. Objective: To synthesize the existing literature on the effect of yoga on pain and quality of life (QOL) in women with CPP. Study Design: PubMed, PEDro, and CINAHL were searched for intervention studies that used yoga to treat women with CPP and reported pain and QOL outcomes. Methods: Effect sizes (ES) and 95% confidence intervals (CI) were calculated from study means and standard deviations for pain and QOL. Individual study ESs were pooled using the fixed-effects or random-effects models for within-group and between-group analyses. Results: Three studies met the inclusion criteria. Statistically significant improvements were seen following the yoga intervention for within-group analysis of QOL (ES =−1.4, CI: −1.8 to 1.1) and pain (ES: −2.2, CI: −2.7 to −1.6). Between-group analysis found statistically significant differences in QOL (ES =−1.5, CI: −2.0 to −1.0) and pain (ES = −1.4, CI: −1.7 to −1.0), favoring the yoga group. Studies varied in dosage and were of low to moderate quality. Conclusion: The results support the use of yoga to improve pain and QOL in women with CPP. Future studies should aim to determine the minimal dosage needed for a successful yoga intervention and use a randomized controlled design with assessor blinding to increase the quality of evidence.